A Comparative Case Study on Performance Management System in Architecture, Engineering, and Construction Start-up Enterprises in Indonesia - Ariono, Bernardus; Wasesa, Meditya; Dellyana, Dina; Dhewanto, Wawan (The Asian Journal of Technology Management (AJTM), 2021)
Abstract. Despite a growing sense that start-up enterprise is critical to economic growth, the topic of performance management affects strategic and organizational processes remains largely understudied. In Indonesia, as a sphere where the entrepreneurial ecosystem is on the rise, we explored the strategy of Architecture, Engineering, and Construction (AEC) start-up firms using a Balanced Scorecard (BSC). This research aims to determine how suitable the BSC is applied to AEC start-ups and how this tool is implemented as the enterprise evolves. We conduct in-depth case studies using multiple data sources, including interviews and field observation. By performing the comparative analysis, we identified managerial practices that enable the networking of BSC perspectives – learning and growth, internal process, customer, and financial – during the start-up lifecycle. From the contribution to the literature perspective, this study provides empirical evidence that the BSC is a valuable performance management tool for early-stage firms. However, the BSC must be reconfigured regularly to reflect the current development stage’s objectives throughout implementation. As the business implications, this research helps AEC entrepreneurs see the significance of achieving organizational balance to drive growth and transition from agile start-ups to sustainable companies. Future research may examine the interconnection between managerial control systems and leadership attributes in different business contexts.Keywords:  AEC firms, Balanced Scorecard, Performance Management System, Start-up Lifecycle